Soybean foliar fertilization: NPK, micronutrients and tillage effects - Rosolem, C. A.; Silvério, J. C.O.; Primavesi, O. (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out on a Dark-Red Latosol Orto at Paranapanema, SP, Brazil, to study the effects of fertilization on soybeans (Glycine max (L.) Merrill), cv. UFV-1, with micronutrients applied or not to the seeds, in two tillage methods: plowing + disking, and subsoiling + disking. The foliar treatments were: 1. control; 2. three applications of 5 l/ha of the formula 5-15-5 at 30, 45 and 60 days from seedling emergence, plus 5 l/ha of the formula 14-4-7 at 75 days from seedling emergence; 3. two applications of 5 l/ha of 5-15-5 plus micronutrients at 45 and 60 days from seedling emergence; 4. two applications of 5 l/ha of 5-15-5 at 45 and 60 days from seedling emergence; 5. idem treatment 4, utilizing 10 l/ha; 6. idem treatment 3, utilizing 10 l/ha. A sub-subplot experimental design was used in all these treatments. An effect of tillage on soybean yield was noticed, which was higher on the plots where the soil was subsoiled and disked. There were not significative effects of micronutrients or foliar fertilization on soybean yields.